Uneven and combined development and unequal exchange: the second wind of neoliberal ‘free trade’? - Bieler, Andreas; Morton, Adam David (Taylor & Francis, 2014)
With capitalist social relations emerging in a prior system of absolutist states in Europe, the outward expansion of capitalism through conditions of uneven and combined development became dependent on the existence of multiple political entities. States in turn are brought into relations of unequal exchange within the global economy. This article analyses the way in which current neoliberal ‘free trade’ policies are related to these fundamental capitalist dynamics, deepening further processes of uneven and combined development as well as unequal exchange.